Pragmatic barriers for delay in access to HCV testing services: Perspective of People With Injecting Drugs and living with HIV - Varada Jayant Madge; Ruchi Sogarwal; Sunil Mehra (Social Medicine Publication Group, 2017)
Background: Hepatitis C (HCV) is emerging as a major public health problem and its co-infection with HIV is on the rise especially in People With Injecting Drugs (PWID). Barriers for delay in accessing services for HCV care may lead to disease progression and impact the society in the form of loss of productive workforce. Aim: This qualitative research was undertaken to explore the barriers for delay in testing for HCV amongst PWIDs. Methods and Material: The study was conducted in two districts of India i.e. Imphal (Manipur state) and Amritsar (Punjab state). A total of 32 PWIDs participated through In-Depth Interviews (IDI) and Focus Group Discussions (FGD). Results: Mostly, the barriers reported for delay in HCV testing were related to socio economic context in which the PWIDs live; inhibitions to get tested due to fear of a positive result, unavailability of HCV services particularly in rural and remote areas, financial costs and long waiting period. Drug use amongst females influenced care seeking behavior. Conclusion: PWIDs face significant health risks of HCV. The socio economic and health systems related barriers create gap for continuum of care for PWIDs. Supportive role of the health care providers, awareness on viral hepatitis, care and support from family is thus fundamental to PWIDs living a healthy life. Key words: Barriers, Hepatitis C Virus, PWID, Health Systems and continuum of care.